How do microbiology consultants undertake their jobs? A survey of consultant time and tasks in South West England. Issue 10 (1st October 2002) - Riordan, T; Cartwright, K; Logan, M; Cunningham, R; Patrick, S; Coleman, T
Abstract : Aims: To measure the total consultant medical microbiologist (CMM) weekly workload, to identify time spent on different activities, and to differentiate those tasks that were viewed by a consensus of consultants as core activities from those that could be accorded a lower priority. Methods: A self administered questionnaire completed by consultant medical microbiologists in the Public Health Laboratory Service South West Group. Results: Reported hours worked by respondents ranged from 41 to 65 hours each week, excluding on call activities. Eleven of 20 respondents reported working in excess of 48 hours each week. There was no correlation between hours worked and laboratory workload as measured by numbers of specimens. Clinical liaison, result authorisation, infection control, and management activities took up most time. Working practices varied widely between individuals, partly reflecting their differing roles in the laboratory. A consensus was reached regarding the relative importance and priority of many regular CMM activities. Conclusions: Consultant microbiologists can identify, with consensus, both high and lower priority activities in their daily practice. If such clinical priorities can be more widely agreed across the profession, this would provide a rational approach to workload control.